(untitled) (Papeles, 2025)
This paper analyzes the social policies implemented in the province of Santiago del Estero during the first Peronist government (1946-1952). It can be observed how these policies operated as strategies of integration, control and consensus, while partially guaranteeing access to basic rights and improvement in indicators related to the living conditions of the population. There are different schools of thought about the meaning of the social policy of the Peronist government; thus, for those who would benefit from the redistribution policy, the social action of the government was an element of dignity, a recognition of their social rights. On the other hand, for those sectors opposed to Peronism, it was only a demagogic attitude to please the impoverished sectors with the aim of expanding the electoral base of Peronism; as a political strategy that would generate expenses for the State. Beyond any position, we will see that the province was far from achieving these goals, which could be due to the fact that the programs designed by the National Government to reduce social inequalities were not adjusted to the reality of the region.